Association between VDR gene FokI polymorphism and renal function in patients with IgA nephropathy - Man-Qiu Mo; Ling Pan; Lin Tan; Ling Jiang; Yong-Qing Pan; Fu-Ji Li; Zhen-Hua Yang; Yun-Hua Liao (PeerJ, 2019)
Background Studies have shown that the occurrence and development of IgA nephropathy (IgAN) are genetically susceptible, but the relationship between vitamin D receptor (VDR) gene polymorphisms and renal function in IgAN patients is unclear. Methods We investigated the relationship between VDR FokI (rs2228570) single nucleotide polymorphism (SNP) and renal function and related clinicopathologic parameters in IgAN patients. Clinical and pathological data of 282 IgAN patients treated at the First Affiliated Hospital of Guangxi Medical University were collected, and FokI genotypes were determined by PCR and direct sequencing. Patients were divided into the renal dysfunction group and normal renal function (control) group by estimated glomerular filtration rate (eGFR) and serum creatinine level. Results Frequencies of TT genotype and T allele in the renal dysfunction group were higher than those of the control group. Blood urea nitrogen, serum phosphorus (P), proportions of mesangial cell proliferation, interstitial fibrosis/tubular atrophy and crescents in T allele carriers were higher than those in non-T allele carriers, while eGFR and 25-Hydroxyvitamin D3 were lower in T allele carriers than non-T allele carriers. Multiple linear regression analysis showed that eGFR was affected by FokI genotypes in IgAN patients. Logistics regression analysis showed that middle and elderly age, elevated P, intact parathyroid hormone and TT genotype were independent risk factors for renal dysfunction in IgAN patients; the odds ratio of carrying the TT genotype was as high as 84.77 (P < 0.05 for all). Conclusions IgA nephropathy patients carrying the VDR FokI TT genotype have an increased risk of renal dysfunction. VDR FokI SNP is closely related to renal function, calcium-phosphate metabolism, and related pathological damage in IgAN patients.